Hubungan Dukungan Keluarga dengan Motivasi Lanjut Usia (Lansia) Mengikuti Program Pengelolaan Penyakit Kronis (Prolanis) - Sari, Wahyu Firman; Zulfitri, Reni; Rustam, Musfardi (Innovative: Journal Of Social Science Research, 2025)
Introduction: The increase in the elderly population shows that the life expectancy of the elderly is also increasing, but this raises the problem of increasing chronic diseases in the elderly. Prolanis is a health service with a proactive, integrated approach involving participants, health facilities and BPJS health to address chronic disease problems in the elderly. One of the things that influences the use of Prolanis health services is family support and motivation of the elderly. Method: This research uses a descriptive correlational research design using a cross sectional approach. The research sample was 85 respondents taken based on inclusion criteria using purposive sampling technique. This study used a questionnaire on family support and motivation for elderly people in participating in Prolanis activities. The analysis used is bivariate analysis using the chi square test. Results: Family support for Prolanis is high (51.8%) and elderly motivation for Prolanis is low (58.8%). Through statistical tests, data was obtained that there was a relationship between family support and the motivation of elderly people to take part in the Chronic Disease Management Program (Prolanis) at the Pekanbaru City Health Center with a p value = 0.005 and the research odds ratio was 4.079. Conclusion: There is a relationship between family support and the motivation of elderly people to take part in the Chronic Disease Management Program (Prolanis) at the Pekanbaru City Health Center.